The Analysis of English Teacher Talk Modification in Classroom Interaction of 2nd Grade Students at MTsN 6 Kubang Putiah - Maryaty, Sri; Melani, Melyann; Reflinda, Reflinda; Roza, Veni (Pusdikra-Publishing.com, 2024)
This research was due to some problems that were found in MTsN 6 Kubang Putih. First, teacher gave less pauses during her talk in the classroom. Teacher talk should be give more pauses for students’ comprehension. Second, the teacher did not do self-repeat frequently. She only does it sometimes. Self-repeat in teacher talk also need to be done frequently. Self-repeat is when the teacher repeat her sentence or word for the students to get a better understanding. This research was descriptive qualitative. , the subject of the research is the teacher and students of English class of the second grade in MTsN 6 Kubang Putih in academic year 2021. There is six class and one class consist of 30 students. The researcher focused on teacher’s talk in the classroom interaction in English class. The researcher used purposive sampling to choose the student to be interviewed or participant. The data of the present study are collected through observation in the classroom and conducting interview. The researcher found that the modifications seen in teacher talk in language classrooms, including a slower rate of speech, longer and more frequent pauses, exaggerated and simplified pronunciation, more basic vocabulary, less subordination, more declaratives and statements versus questions, and more self-repetition, were all present. This supports the findings from Chaudron and Dodu's study of modification of teacher talk in language classrooms. The findings of this research highlighted the importance of teacher modifications in language teaching. It is essential for teachers to vary their speech rate, use pauses, and stress particular words in order to emphasize the messages they are trying to communicate within the classroom. Self-repeat can aid learners in understanding the instructional content better. Additionally, teachers should incorporate simple vocabulary within their discussions, and use more declarative senteces. Modifying the teacher talk is an effective strategy in helping learners better comprehend the material being presented.